One percent terror, ninety-nine percent boredom: an analysis of the military boredom and leisure time experiences of SADF soldiers during the South African Border War 1966–1989 - Eriksen, Garrett Ernst (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.